Interaction study of muscle laceration and cortical bone fracture in opened fracture / M.S. Salim - Salim, M.S.; Azizan, N.A.A.; Salleh, A.F.; Daud, R. (Universiti Teknologi MARA, Perlis, 2018)
Generally, open fracture is classified when there is an observable open wound on the region of broken bone. Initially, this research was carried out to dig out answers and solutions for problems and issues that had arises for centuries. One of the problems is the difficulty to observe the mechanical properties attained by the four layers when the samples of bone and muscle are difficult to be handled. On the other hand, there is no research has been conducted yet to analyse the behaviour of bone fracture and muscle laceration during opened fracture. The primary objective of this research is to develop a two-dimensional (2D) model of human muscle and cortical bone segment by using finite element software (ANSYS 14). Upon the development of this multilayer model, the mechanical properties of cortical bone and muscle were considered. Moreover, this research was to determine and analyse the parameters of stress intensity factor, strain-energy release rate and Von Mises stress when three-point bending test is applied on the developed 2D multilayer model that consist of muscle and cortical bone layers by using continuum mechanics approach. By referring to the previous research papers, the dimension of the model is determined and the construction of 2D numerical model was done. Different loads and crack-to-width ratios were two manipulative variables applied in this research in order to evaluate the required corresponding variables. It is found that the stress intensity factor and strain-energy release rate obtained from finite element analysis were increased due to the increasing of crack length and applied loads. Furthermore, the Von Mises stress gained from the developed numerical model also have the same pattern, which increased with the increment of crack lengths.